Relevansi I’jazul Qur’an dalam Tantangan Modernitas - Rohman, Taufikur (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This study examines the relevance of the Qur'an in facing modern challenges with the aim of exploring the relevance of the Qur'an in three main dimensions: linguistic, scientific, and socio-ethical. This study uses a literature review method with a descriptive-analytical approach. The data sources consist of the Qur'an, classical and contemporary interpretations, as well as scientific articles relevant to. The analysis is carried out through thematic identification. The results of the study show that the linguistic dimension of the Qur'an reflects a unique, precise, and cohesive language structure that surpasses human capabilities. Its scientific dimension shows the harmony between revelation and science, especially in the fields of embryology and astronomy, without compromising its spiritual value. Meanwhile, the social and ethical relevance of the Qur'an offers practical guidance for building a just, inclusive, and moral society. This finding emphasizes that I’jazul Qur’an is an eternal miracle that is able to answer the challenges of the times. The conclusion of this study confirms that I’jazul Qur’an, through the integration of these three dimensions, can be a multidimensional solution in facing the challenges of modernity.